OPTIMASI RENCANA OPSI SAHAM KARYAWAN DALAM MENCAPAI KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Sub Sektor Kimia, Konsumsi, dan Aneka Industri yang Terdaftar di Bursa Efek Indonesia periode 2017 – 2020) - Aulia Nur Azahra Setiyadi; Rita Wijayanti (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aimed to examine the effects of Intellectual Capital with the proxies of Capital Employee (CE), Human Capitan (HC), and Structural Capital (SC) on the company's financial performance. It also examines the impact of implementing the Employee Stock Option Plan and Intellectual Capital on the company's financial performance. The data used in this study came from the published annual financial statements of each company that became the research sample. The population of this study is manufacturing companies that implement the Employee Stock Option Plan program on the Indonesia Stock Exchange (IDX) with a research period from 2017 to 2020. The research sample is 36 companies, based on the criteria the number of companies that meet the sample criteria are 9 companies. . This study uses multiple linear regression analysis techniques to analyze the data. The results show that human capital and employee stock option plans have an effect on the company's financial performance. Stock-based compensation has an impact on the effect of employee capital on the company's financial performance